2017
DOI: 10.1101/cshperspect.a026518
|View full text |Cite
|
Sign up to set email alerts
|

TET2 in Normal and Malignant Hematopoiesis

Abstract: The ten-eleven translocation (TET) family of enzymes were originally cloned from the translocation breakpoint of t(10;11) in infant acute myeloid leukemia (AML) with subsequent genomic analyses revealing somatic mutations and suppressed expression of TET family members across a range of malignancies, particularly enriched in hematological neoplasms. The TET family of enzymes is responsible for the hydroxylation of 5-methylcytosines (5-mC) to 5-hydroxymethylcytosine (5-hmC), followed by active and passive mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 72 publications
2
62
0
Order By: Relevance
“…142,143 Integration site analysis revealed that the virus disrupted the function of TET2, a gene involved in epigenetic modification which is also associated with myeloid malignancies. 144 This finding highlights that viral integration-induced gene disruption remains a clinical possibility, albeit a rare one. Second, integrating viruses leave the endogenous TCR intact, providing a "sink" for limiting intracellular signal transduction molecules, including CD3 and Lck.…”
Section: Non-viral Tcr Integration Strategiesmentioning
confidence: 91%
“…142,143 Integration site analysis revealed that the virus disrupted the function of TET2, a gene involved in epigenetic modification which is also associated with myeloid malignancies. 144 This finding highlights that viral integration-induced gene disruption remains a clinical possibility, albeit a rare one. Second, integrating viruses leave the endogenous TCR intact, providing a "sink" for limiting intracellular signal transduction molecules, including CD3 and Lck.…”
Section: Non-viral Tcr Integration Strategiesmentioning
confidence: 91%
“…EZH2 is affected by somatic gainof-function mutations in 30% of GCB-DLBCL and FL patients. 118 Gene promoter 5mC is linked to transcriptional repression, whereas 5hmC is a transcriptional activation mark at gene enhancers ( Figure 2). Y641 mutant EZH2 yields more efficient H3K27 trimethylation but loss of H3K27 monomethylation activity.…”
Section: Core Epi G Ene Tic Mechanis Ms Driving G C-derived Lymphommentioning
confidence: 99%
“…39,57 TET2 is an alpha-ketoglurate (aKG)-dependent dioxygenase that converts 5'methylcytosine (5mC) into 5'hydroxymethylcytosine (5hmC). 118 Gene promoter 5mC is linked to transcriptional repression, whereas 5hmC is a transcriptional activation mark at gene enhancers ( Figure 2). 119 Loss of Tet2 results in GC hyperplasia in mice and failure to undergo class-switch recombination and plasma cell differentiation, ultimately leading to the development of B-cell lymphomas.…”
Section: Core Epi G Ene Tic Mechanis Ms Driving G C-derived Lymphommentioning
confidence: 99%
“…Mutations in TET2, ASXL1, and SRSF2 tended to co-occur with mutations in at least one other gene with 37 of the 42 TET2 mutations occurring in samples with additional mutations, in keeping with its role as a driver of myeloid cancers. 36 The most commonly co-occurring mutation pair was between JAK2 and TET2 (Figure 2C; Tables S8 and S9).…”
Section: Variant Assessment In Patient Samplesmentioning
confidence: 99%